Project complexity and how to effectively measure complexity in projects: the case of a refuelling outage in a nuclear power generating plant - Mabumbulu, Noxolo (Department of Construction Economics and Management, 2017)
Background: Projects have become larger, technologically more sophisticated and are organised with a higher number of contractors and partners, compared to 40 years ago. The majority of large, complex capital projects often incur significant cost/budget and schedule overruns. Delays and cost overruns are seemingly, the rule rather than an exception these days. Research shows that one of the reasons for project failure is the increasing complexity of projects or an underestimation of the project complexity. There is therefore a fundamental need to develop a tool or model that will assist project managers to measure complexity within their projects Research Purpose: To define project complexity, develop a model or tool to measure complexity within projects and to improve the understanding of the dimensions of project complexity. Research Methodology: The case study methodology was employed, and the unit of analysis was the refuelling outage in a nuclear power generating plant. Focus group was adopted as a technique to gather information. A group of project managers with wealth of knowledge in refuelling outages were assembled. They were given the complexity assessment matrix to assess their respective subprojects, in order to rate the refuelling outage project Findings: Two main scientific approaches to project complexity, namely; descriptive complexity and perceived complexity were established. Descriptive complexity considers complexity as an intrinsic property of a system. Perceived complexity considers complexity as subjective, since the complexity of a system is understood through the perception of an observer and both approaches can coexist. There are vital layers of complexity such as: social, cultural, operative and cognitive complexity that must be considered when dealing with complexity within projects. A three dimensional model that encompasses the complexity dimensions (origin of project complexity), severity factors (the extent to which complexity dimension will be a problem) and the nature of interdependences (pooled, sequential, and reciprocal) was developed. This model was used to assess complexity of the refuelling outage in a power generating plant. The results of this assessment indicated that this project is a very complex project.